Simultaneous non‐invasive epicardial and endocardial mapping in patients with brugada syndrome: new insights into arrhythmia mechanisms - Rudic, Boris; Tueluemen, Erol; Papavassiliu, Theano; Dösch, Christina; Liebe, Volker; Kuschyk, Jürgen; Röger, Susanne; El-Battrawy, Ibrahim; Akın, Ibrahim; Borggrefe, Martin (Journal of the American Heart Association, 2016)
BackgroundThe underlying mechanisms of Brugada syndrome (BrS) are not completely understood. Recent studies provided evidence that the electrophysiological substrate, leading to electrocardiogram abnormalities and/or ventricular arrhythmias, is located in the right ventricular outflow tract (RVOT). The purpose of this study was to examine abnormalities of epicardial and endocardial local unipolar electrograms by simultaneous noninvasive mapping in patients with BrS.Methods and ResultsLocal epicardial and endocardial unipolar electrograms were analyzed using a novel noninvasive epi‐ and endocardial electrophysiology system (NEEES) in 12 patients with BrS and 6 with right bundle branch block for comparison. Fifteen normal subjects composed the control group. Observed depolarization abnormalities included fragmented electrograms in the anatomical area of RVOT endocardially and epicardially, significantly prolonged activation time in the RVOT endocardium (65±20 vs 38±13 ms in controls; P=0.008), prolongation of the activation‐recovery interval in the RVOT epicardium (281±34 vs 247±26 ms in controls; P=0.002). Repolarization abnormalities included a larger area of ST‐segment elevation >2 mV and T‐wave inversions. Negative voltage gradient (−2.5 to −6.0 mV) between epicardium and endocardium of the RVOT was observed in 8 of 12 BrS patients, not present in patients with right bundle branch block or in controls.ConclusionsAbnormalities of epicardial and endocardial electrograms associated with depolarization and repolarization properties were found using NEEES exclusively in the RVOT of BrS patients. These findings support both, depolarization and repolarization abnormalities, being operative at the same time in patients with BrS.